Attitude of Vegetable Growers Towards Organic Farming Practices (Indian Journal of Extension Education, 2009)
The study was undertaken in Thiruvananthapuram district. One hundred vegetable growers were selected by using the proportionate random sampling technique. Sixteen independent variables were selected based on judges’ relevancy rating and were quantified using measurement devices. The data were collected using a pre testeci structured interview schedule and suitable statistical tools were used to analyze the data. Majority of the respondents (64%) had a favourable attitude. Seven variables, namely, mass media exposure, innovativeness, market perception, self confidence, environmental orientation, awareness and knowledge showed a significant and positive relationship with attitude towards organic farming practices. Attitude is very important for success organic farming practices.